The role of the glucosensing receptor TAS1R3 in glioblastoma, breast, and colorectal cancer hallmarks - Matos, Inês Rosado de (2023)
Glucose metabolism plays a critical role in cancer cells, with oncogenes and tumour suppressor genes regulating key enzymes involved in glycolysis. This metabolic rewiring, known as the Warburg effect, shifts cancer cells' energy production from oxidative phosphorylation to aerobic glycolysis, increasing glucose uptake and lactate fermentation support cancer cell proliferation, growth, and survival. The taste receptor signalling, specifically the sweet taste receptor composed of TAS1R2 and TAS1R3 subunits, is expressed in various extra-oral tissues, including cancer cells, where they are involved in cellular processes such as proliferation and apoptosis. Thus, the sweet taste receptor could be an interesting target for cancer therapeutic research. Cancer remains a significant global health concern, continuously requiring research for new treatments and therapeutic targets. Breast cancer, colorectal cancer, and glioblastoma pose significant challenges due to their high mortality rates and limited treatment options, particularly in the case of glioblastoma. Surgical resection, radiotherapy, and chemotherapy often fall short in achieving desirable outcomes. Therefore, exploring alternative therapeutic targets, in these cancer types holds great relevance. This dissertation aims at extending our research group preliminary findings in glioblastoma, investigating the role of the glucosensing receptor TAS1R3 in glioblastoma, breast, and colorectal cancer hallmarks. More specifically, this study aims at determining the effect of TAS1R3 inhibition with lactisole on cell senescence, lactate production, and glucose uptake in breast cancer (MCF7), colorectal cancer (Caco-2), and glioblastoma (U-87MG, SNB-19, and U-373MG) cell lines. We first confirmed the expression of both sweet taste subunits (TAS1R2 and TAS1R3) in all cell lines in study. Additionally, we found that TAS1R3 inhibition with lactisole decreased the glucose uptake by glioblastoma and breast cancer cells. In addition, the TAS1R3 inhibition also led to decreased L-lactate extracellular levels in colorectal cancer and glioblastoma cells. However, TAS1R3 inhibition with lactisole did not trigger senescence in any of the cell lines in study. These results suggest a potential role of TAS1R3 in modulating these metabolic processes in breast, colorectal and glioblastoma cells. Additionally, these findings contributed to our understanding of the complex interplay between the sweet taste receptors, glucose metabolism, and cancer hallmarks, highlighting the potential therapeutic implications of targeting TAS1R3 in tumours.